The Estimation of Dental Arch Discrepancy Among Libyan Adolescents and Adults with Irregular Teeth. - Ben-omran, Ahmed (Khalij-Libya Journal of Dental and Medical Research, 2025)
The objective of this clinical study was to estimate the amount of dental discrepancy in patients seeking orthodontic treatment to correct irregular and crowded teeth in the Region of Misurata, to know the severity of the problem and the possibility of prevention and treatment, and to provide data for future comparisons with other regions in Libya. 120 orthodontic diagnostic models (60 males and 60 females aged from 14-24 years) from the authors’ courtesy for patients with a Class I malocclusion and a full set of permanent teeth (except third molars) were manually analyzed using the segmented arch approach for space analysis. To test the intra-examiner reliability, 20 modes were randomly selected and analyzed twice in a one-week interval. The difference between the two measurements was tested using a sample t-test, and the difference was statistically not significant (p=0.832). Statistical analysis was done using SPSS version 7.5 software (LEAD Technologies Inc). There was neither a difference between males and females nor an age influence regarding the severity of dental crowding. The mean dental discrepancy of the upper and lower jaws, respectively, are (-4.60± 2.90 and -4.96±3.05 mms), indicating that generally the studied sample has a severe dental discrepancy in both jaws (space deficiency> 4 mms). >50% of the studied group showed a severe crowding (space deficiency >4mms), >35% had a moderate crowding (space deficiency > 2≤ 4mms). There is a strong correlation between the total discrepancy and the amount of discrepancy at the canine premolar segment (r>0.7 p<0.01) suggesting that arch perimeter loss due to premature loss of primary teeth may be the major etiologic factor among the study sample, but further studies are needed to explore other possible factors. الهدف من هذه الدراسة السريرية تقدير مقدار عدم الأنتظام السني (أزدحام الأسنان) في المرضى الذين يريدون إجراء العلاج التقويمي لتصحيح الأسنان غير المنتظمة والمزدحمة في منطقة مصراتة، لتحديد شدة المشكلة وإمكانية الوقاية والعلاج، وتقديم بيانات للمقارنة المستقبلية مع مناطق أخرى في ليبيا. تم تحليل 120 نموذجًا تشخيصيًا تقويميًا (60 ذكرًا و60 أنثى، تتراوح أعمارهم بين 14 و24 عامًا) من ضمن عيادة المؤلف للمرضى الذين يعانون من سوء الإطباق من النوع الأول، ولديهم مجموعة كاملة من الأسنان الدائمة (باستثناء الأضراس الثالثة)، باستخدام طريقة القوس المجزاء لتحليل المسافة. من أجل اختبار موثوقية الفحص لنفس الفاحص (المؤلف)، تم اختيار 20 نموذجًا عشوائيًا وتحليلها مرتين بفاصل زمني أسبوع واحد بين القياسين و تم اختبار الفرق بين القياسين باستخدام اختبار t المزدوج، وأظهرت النتائج عدم وجود فرق ذو دلالة إحصائية . (p = 0.832). تم إجراء التحليل الإحصائي باستخدام برنامج SPSS الإصدار Lead Tech. Inc) 7.5 ( لم يكن هناك فرق ملحوظ في شدة ازدحام الأسنان بين الذكور والإناث، كما لم يكن للعمر تأثير في شدة الازدحام. كان المتوسط العام لعدم الأنتظام السني أو أزدحام الأسنان السني في الفك العلوي والسفلي على التوالي -4.60 ± 2.90 مم و -4.96 ± 3.05 مم، مما يشير إلى أن العينة المدروسة عمومًا تعاني من أزدحام سني شديد (نقص المسافة > 4 مم) في كلا الفكين. أظهر أكثر من 50% من المجموعة المدروسة ازدحامًا شديدًا (نقص المسافة > 4 مم)، بينما كان أكثر من 35% يعانون من ازدحام معتدل (نقص المسافة بين 2 و 4 مم). لوحظ ارتباط قوي بين الأزدحام الكلي والأزدحام في منطقة القواطع والأضراس الأمامية (r > 0.7، p < 0.01)، مما يشير إلى أن فقدان محيط القوس بسبب الفقدان المبكرللأسنان اللبنية قد يكون العامل المسبب الرئيسي في هذه العينة. ومع ذلك، هناك حاجة إلى دراسات إضافية لاستكشاف العوامل المحتملة الأخرى